Consumer preferences in young adults in urban locations: impulsive or reasoned purchases? - Flor Freire, Ximena (2019)
The tastes and preferences of consumers are constantly changing and are influenced by the environment, especially those of the young adult of 20 to 29 years named millennial, characterized by its creativity and technological connectivity, whose purchasing decisions set market trends. The objective of the study is to describe their consumption preferences in the urban parishes of the city of Quito and contrast the spending paradigms. The research is descriptive, quantitative and transversal; the methodology based on the inductive method was applied to a sample of 188 young adults. This age group makes its purchasing decisions in a reasoned and critical manner. Their main motivation is based on quality, with food, housing and study as a priority for consumption. DOI: https://doi.org/10.31164/bcoyu.23.2019.844 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/844